Poverty In Indonesia: Critical Review - Idrus, Syech; Rosida, Lia (Archives of Business Research, 2020)
This article critically review the information regarding poverty issues in Indonesia, by unravelling the causes and impacts of poverty and its aggregates comprising rural poverty, women and poverty, as well as other social indicators. This review article based on data provided in secondary resources shows that Asian Financial crisis in 2008 was regarded as the greatest intrusion of economic stability, rendering more adverse poverty incidences in Indonesia. Although Indonesia could slowly recover from the crisis, poverty remains problematic for certain groups and women in some particular areas especially rural areas. Moreover, despite several policies have been stipulated to deal with poverty such as Rural Development Program and Social Safety Net, some poverty elements related to social capital such as education, employment and health need to be improved. Thus, Indonesian government should pay more attention to improve the quality of the provisions and policies, assuring the beneficial contribution to Indonesian citizens’ welfare.